Dietary and Nutritional Supplementation for Painful Diabetic Neuropathy: A Narrative Review - Apergi, Kyriaki; Papanas, Nikolaos (Experimental and Clinical Endocrinology & Diabetes, 2023)
Painful diabetic neuropathy (PDN) is a serious and very common complication of diabetes mellitus (DM). It negatively affects the quality of life, increases morbidity and poses a financial burden on the health care system. Currently, treatment of PDN focuses on glycaemic control, while pathogenesis-oriented therapy has not yielded satisfactory results. The need to improve therapy remains. There is accumulating evidence on the potential benefit of nutritional interventions. This narrative review aims to examine the potential benefit of dietary and nutritional supplementation for PDN management. According to the preliminary research, supplementation with vitamin E, B-complex, omega-3 fatty acids, CoQ10 or N-acetylcysteine seems to be associated with promising results in improving PDN symptoms.
Keywords: diabetes mellitus; diet; nutrition; painful diabetic neuropathy; supplement